Nhận thức của sinh viên ngành Giáo dục mầm non về các rào cản trong giao tiếp bằng tiếng Anh: Nghiên cứu tại hai trường đại học ở Hà Nội - Đặng Út, Phượng; Nguyễn Thị Mai Thương, Nguyễn Thị Mai Thương (Tạp chí Giáo dục, 2026)
This cross-sectional study examined Early Childhood Education students’ perceptions of barriers to communicating in English at two universities in Hanoi. Data from 473 valid questionnaires were analyzed using reliability analysis, confirmatory factor analysis (CFA), the heterotrait-monotrait ratio (HTMT), descriptive statistics, Friedman and Wilcoxon tests, and one-way ANOVA with Tukey post-hoc comparisons. The 15-item instrument supported a three-correlated-domain model comprising linguistic, psychological, and learning-environment barriers (χ²(87) = 359.86, CFI = .952, TLI = .942, RMSEA = .082, SRMR = .045); standardized loadings ranged from .769 to .865. HTMT between linguistic and psychological barriers was .883, indicating substantial conceptual overlap. The overall reported barrier score was above the scale midpoint (M = 3.643, SD = .687). Linguistic barriers had the highest mean (M = 3.700), although differences across domains were very small (Kendall’s W = .017). Students with lower self-rated English communication ability reported higher barriers, F(3,469) = 11.331, p < .001, η² = .068. The findings provide evidence supporting a profession-sensitive three-domain approach to interpreting future preschool teachers’ self-reported barriers to communicating in English; however, the cross-sectional self-report design does not permit causal inference or replace direct assessment of communicative performance.